Computational Modeling and Simulation of Solids and Structures: Recent Advances and Practical Applications - Kim, Jin-Gyun; Lim, Jae Hyuk; Persson, Peter (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Computational modeling and simulation are essential to solid and structural mechanics. They have not only covered entire engineering fields (civil, aerospace, mechanical, etc.) but also various scales (from nano to macro) and physics (mono- and multiphysics). Recently, they have been found to be able to offer theoretical backgrounds of digital transformation. Society at large is increasingly enthusiastic about data-driven modeling and simulation, and the possibilities they offer. The aim of this Special Issue reprint was to provide a forum for researchers to discuss recent advanced computational modeling and simulation techniques of solids and structures, and applications to solve challenging engineering problems.